2002
DOI: 10.1039/b111271f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound promoted Suzuki cross-coupling reactions in ionic liquid at ambient conditions

Abstract: Palladium catalyzed Suzuki cross-coupling reactions of halobenzenes including chlorobenzenes with phenylboronic acid have been achieved at ambient temperature (30 degrees C) in the absence of a phosphine ligand using the ionic liquid 1,3-di-n-butylimidazolium tetrafluoroborate [bbim][BF4] with methanol as co-solvent under ultrasonic irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(82 citation statements)
references
References 7 publications
2
77
0
3
Order By: Relevance
“…[1][2][3][4] Recent research has focused on air-stable, room-temperature ionic liquids composed of asymmetric N,N′-dialkylimidazolium cations with a variety of bulky anions such as PF 6 -and BF 4 -. These ionic liquids exhibit unique properties, including high thermal stability, large liquid range, and negligible vapor pressure.…”
mentioning
confidence: 99%
“…[1][2][3][4] Recent research has focused on air-stable, room-temperature ionic liquids composed of asymmetric N,N′-dialkylimidazolium cations with a variety of bulky anions such as PF 6 -and BF 4 -. These ionic liquids exhibit unique properties, including high thermal stability, large liquid range, and negligible vapor pressure.…”
mentioning
confidence: 99%
“…[14][15] Further, ultrasound is an alternative energy source to accelerate organic transformations ordinarily through heating instead of harsh conventional heating. 16 In the literature many homogeneous and heterogeneous catalyzed organic reactions 17 have established competently proceed via the formation and adiabatic collapse of transient cavitation bubbles in ultrasonication 18 by overcoming some of the demerits exposed in conventional methods. The remarkable advantages in the ultrasound irradiations are decrease the reaction time, increase the rate of the reaction, the yield enhancement of products with high purity, high efficiency and waste minimization.…”
Section: Figure 1some Biologically Active Urea and Thiourea Derivatimentioning
confidence: 99%
“…Further, our attention was focused to reduce the reaction time; hence, the optimized reaction was carried out in ultrasonication at 40 o C (Table 1 entry 19) and observed remarkably high yield of the product 6b (87%) in short reaction time (25 min.). Yet again to distinguish the temperature effect on the yield of the product, the model reaction was investigated at ambient temperature and different temperatures (Table 1 entry [17][18][19][20]. As seen in the table, it was found that the reaction is proceed at 40 ºC and afforded high yield (81%) of the product in less time (25 min) and significant yield enhancement was observed upon increasing the temperature until 50 o C, and no noteworthy enhancement at 60 o C. It is well known that the amount of catalyst also play an important role in the reaction, so, the model reaction was tested in PEG-400 by loading different amounts of the catalyst, 37% nano-BF 3 -SiO 2 under conventional and ultrasonication conditions and the results are presented in Table 2, entry 1-5.…”
Section: Chemistrymentioning
confidence: 99%
“…117,118 The substituted chlorobenzenes which generally do not undergo Pd catalyzed coupling unless it is activated, reacts with phenylboronic acid at ambient temperature (30 °C) in IL [bbim] [BF 4 ] under ultrasonic irradiation. 118 The sonochemical reactions were carried out in a thermostated ultrasonic cleaning bath of frequency 50 kHz (Branson 5200). Since the phenylboronic acid was insoluble in the IL under the reaction conditions, the sonochemical reaction was performed in the IL with methanol as cosolvent, which resulted in a homogeneous solution and complete conversion.…”
Section: Suzuki Couplingmentioning
confidence: 99%
“…But, recycling of the catalyst is possible if Pd-biscarbene complex (3) is used as a catalyst. 118 The recovered complex was further used three times for the sonochemical Suzuki reaction of 4-methoxybromobenzene to afford the 4-methoxybiphenyl in 82%, 80% and 75% yields respectively.…”
Section: Suzuki Couplingmentioning
confidence: 99%